Centralized server monitoring implementation using zabbix for system administrator access network management (ANM) Telekom Malaysia Berhad / Putra Omar Teha - Teha, Putra Omar (2015)
Readiness Element Management System (EMS) to monitor access network is critical to TM business. To meet this need the centralized system is needed to monitor the set of servers that have run in various platforms. The latest direction the company want existing workforce can be optimized based on the current business situation. This situation has forced the management of the company to reduce the number of employees in certain parts and lead to labor shortages and the increasing number of systems that need to be taken care of them. This project has been implemented to meet the needs of a System Administrator Telekom Malaysia (TM) representing the administrator to access network systems in Telekom Malaysia (TM). The aim is to lighten the burden on the operator of the system in matters related to the administration systems with a variety of technologies and applications. This project use Zabbix platform is an open source system that is easy to use and does not require high costs for implementation. This has been of interest to me to use Zabbix in implementing a centralized system for monitoring systems that are in inventory TM especially involving access network. With the completion of this project System Administrator will receive an early warning about the state the server via email processed by Zabbix server. Therefore it can help System Administrators to reduce downtime due to hardware damage, system intrusion and other conditions that can cause a system that does not function properly.